Political Economy of Electronic Money in Indonesia, Perspective and Comparison to Singapore. - Hadi, Prasetyo; J, Indri Arrafi; Sinaga, Obsatar (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to find a harmonious understanding of the massive use of electronic money in Indonesia. This research reveals the idea that rapid adoption has shaped the change in traditional payment mechanisms and money creation in central banks and banks. This study uses panel data analysis techniques by analyzing the inflation rate, interest rate, and circulation of electronic money on the level of the money supply compared between the two countries, Indonesia and Singapore. The sampling technique used is saturated sample, saturated sampling technique is a sampling technique in which all members of the population are used as samples. The research sample was taken as many as 80 observations consisting of 2 country objects, namely Indonesia and Singapore from 2011-2020 and using quarterly data. The results of the study show the results in the regional 1 model, namely: (1) Electronic Money Volume has a significant effect on economic growth (2) inflation has a positive and insignificant effect on economic growth (3) interest rates have a significant effect on economic growth (4 ) the state has a significant influence on economic growth and for the results of regression model 2 testing, namely: (1) Electronic Money Volume has a significant influence on the money supply (2) ATM/debit transaction volume has a significant effect on the money supply (3 ) the volume of credit card transactions has a significant effect on the amount of money in circulation (4) countries have a significant influence on economic growth.